Role of dendritic cell‐mediated immune response in oral homeostasis: A new mechanism of osteonecrosis of the jaw. Issue 2 (9th January 2020) - Elsayed, Ranya; Kurago, Zoya; Cutler, Christopher W.; Arce, Roger M.; Gerber, Jennifer; Celis, Esteban; Sultan, Hussein; Elashiry, Mahmoud; Meghil, Mohamed; Sun, Christina; Auersvald, Caroline M.; Awad, Mohamed E.; et al.
Abstract: Dendritic cells are an important link between innate and adaptive immune response. The role of dendritic cells in bone homeostasis, however, is not understood. Osteoporosis medications that inhibit osteoclasts have been associated with osteonecrosis, a condition limited to the jawbone, thus called medication‐related osteonecrosis of the jaw. We propose that disruption of the local immune response renders the oral microenvironment conducive to osteonecrosis. We tested whether zoledronate (Zol) treatment impaired dendritic cell (DC) functions and increased bacterial load in alveolar bone in vivo and whether DC inhibition alone predisposed the animals to osteonecrosis. We also analyzed the role of Zol in impairment of differentiation and function of migratory and tissue‐resident DCs, promoting disruption of T‐cell activation in vitro. Results demonstrated a Zol induced impairment in DC functions and an increased bacterial load in the oral cavity. DC‐deficient mice were predisposed to osteonecrosis following dental extraction. Zol treatment of DCs in vitro caused an impairment in immune functions including differentiation, maturation, migration, antigen presentation, and T‐cell activation. We conclude that the mechanism of Zol‐induced osteonecrosis of the jaw involves disruption of DC immune functions required to clear bacterial infection and activate T cell effector response.